Polymerase chain reaction (PCR) based indexing of black pepper (Piper nigrum L.) plants against Piper yellow mottle virus - C K Thankamani, P A Mathew, A I Bhat, A Siljo, M V Jiby, (Journal of Spices and Aromatic Crops, 2009)
A polymerase chain reaction (PCR) based method was used for indexing 845 plantsrepresenting 14 popular varieties of black pepper (Piper nigrum) showing no visible externalsymptoms (apparently healthy) for Piper yellow mottle virus (PYMoV), among which 694plants were positive (82%) for PYMoV. The percentage of infected plants ranged from 59% to100% in different varieties; 100% of the tested plants of Panniyur-6 were infected with PYMoVand Sreekara had the least number of infected plants (59%). Some of the indexed PCR positiveplants exhibited visible symptoms such as mild chlorosis, yellow specks and mottling in 1-3months after testing. The study showed that indexing by PCR successfully detected PYMoVin infected black pepper plants showing no visible symptoms. The method can be used incertification programmes to identify PYMoV-free plants for further propagation.